2013
DOI: 10.1021/la3043473
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Dynamics of Biological Water in a Single Live Cell under a Confocal Microscope

Abstract: Time-resolved confocal microscopy has been applied to study the cytoplasm and nucleus region of a single live Chinese hamster ovary (CHO) cell. To select the cytoplasm and the nucleus region, two different fluorescent probes are used. A hydrophobic fluorescent dye, DCM, localizes preferentially in the cytoplasm region of a CHO cell. A DNA binding dye, DAPI, is found to be inside the nucleus of the cell. The locations of the probes are clearly seen in the image. Emission maxima of the dyes (DCM in cytoplasm and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 61 publications
3
64
0
Order By: Relevance
“…Inspired by this, we thus attributed higher in nucleus to a larger ratio of free water over bound water in nucleus than in cytoplasm. This qualitative trend indeed finds agreement with earlier spectroscopy results of faster solvation dynamics and more similarity to bulk-water dynamics inside nucleus than in cytoplasm 4144 . Moreover, this attribution is also in the same trend with the concept of macromolecular crowding in which the cytoplasm is found to be somewhat more crowded than the nucleus 45,46 .…”
Section: Resultssupporting
confidence: 91%
“…Inspired by this, we thus attributed higher in nucleus to a larger ratio of free water over bound water in nucleus than in cytoplasm. This qualitative trend indeed finds agreement with earlier spectroscopy results of faster solvation dynamics and more similarity to bulk-water dynamics inside nucleus than in cytoplasm 4144 . Moreover, this attribution is also in the same trend with the concept of macromolecular crowding in which the cytoplasm is found to be somewhat more crowded than the nucleus 45,46 .…”
Section: Resultssupporting
confidence: 91%
“…In addition to the different interactions of NPs with subcellular compartments, the differences in dielectric constants could be another reason for the plasmonic shifts between particles situated in the periphery and particles in the cytoplasm or the nucleus. Some studies show that the cytoplasm of cells has dielectric constants ten times higher than that of the cell membrane 41,44 , and in another study 45 , the dielectric constant of the nucleus was found to be four times higher than that of the cytoplasm. Nanostars tend to aggregate, and their LSPR peaks were broader than those of nanospheres.…”
Section: Np Spectral Responses For Intracellular Diagnosismentioning
confidence: 95%
“…89 Dielectric constants of 15 and 60 were recently determined for the cytoplasm and cell nucleus of mammalian CHO cells, respectively. 90 …”
Section: Physicochemical Properties Of the Intracellular Environmentmentioning
confidence: 99%